PEANGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SD - Dewantara, Dimas; Elizar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of social studies learning in elementary schools still faces various obstacles, such as teacher-centered learning, low student participation, and less than optimal learning outcomes. One alternative that can be applied to overcome these problems is the Group Investigation (GI) learning model, a cooperative learning model that requires active student participation in investigation activities, discussions, collaboration, and presentation of results. This study aims to analyze the effect of the Group Investigation learning model on student learning achievement in social studies learning at the elementary school level. This study applies the Systematic Literature Review (SLR) method as a research approach by analyzing 10 articles of data collected through the Google Scholar database based on inclusion and exclusion criteria in the period 2021–2026. The results of the study show that publications regarding the Group Investigation learning model in social studies learning in elementary schools have experienced quite significant development, with the highest number of publications in 2025 of 585 articles. The results of the synthesis of the ten articles reveal that the implementation of the Group Investigation model consistently contributes positively to social studies learning achievement, increasing students' activeness, participation, ability to collaborate, and critical thinking skills. Based on these findings, the Group Investigation learning model has proven to be effective in implementing social studies learning in elementary schools and is recommended as an innovative learning model to improve the quality of the learning process and student learning achievement.